(untitled) (Práxis Educativa, 2022)
This article proposes to contextualize health education for the black population in the Family Health Strategy in terms of its limits and its possibilities. Since this population is built and rebuilt in the face of society, in which racism predominates in a marked way, where there are territories in which black lives take place, since slavery and even with the prevailing abolition of slavery, racism prevails. However, some movements of struggles in favor of equality and health policies that collaborate for the equity of the black population have emerged. Health education within the Family Health Strategy contributes to the self-care of the black population, which in most cases is invisible. Keywords: Family Health Strategy. Health education. Black population. Racism.